Cisco router code generator (CRCodeG) / Mohd Faiz Jamaludin - Jamaludin, Mohd Faiz (2013)
Cisco Router Code Generator (CRCodeG) – Router needs to configured based on network design include policy that user wants to support device connection smoothly run. However, human mistake such as typo, wrong script code applied and lack of command knowledge like forget only single line of command will affect performance of the network or error at all. To reduce the human mistake and lack of knowledge problem, Cisco Router Code Generator as an online web based system may help to provide complete script command to apply on router configuration. User only need to fill in the form in CRCodeG and system will generate the script command based on requested by user on that form. Operation on the system is using PHP as server site scripting. PHP with their function will produce document file with router configuration for user by download or just view it after generate the form. After script command generated by the system, Packet Tracer will use on development site to test the script command based on visual mini network design on Packet Tracer.